APOE polymorphism as a potential determinant of functional fitness in the elderly regardless of nutritional status - Snejdrlova, Michaela; Kalvach, Zdenek; Topinkova, Eva; Vrablik, Michal; Prochazkova, Renata; Kvasilova, Marie; Lanska, Vera; Zlatohlavek, Lukas; Vaclová, Martina; Ceska, Richard (Neuro-endocrinology letters, 2011)
OBJECTIVES: Life expectancy is determined by a combination of genetic predisposition (~25%) and environmental influences (~75%). Nevertheless a stronger genetic influence is anticipated in long-living individuals. Apolipoprotein E (APOE) gene belongs among the most studied candidate genes of longevity. We evaluated the relation of APOE polymorphism and fitness status in the elderly. MATERIAL AND METHODS: We examined a total number of 128 subjects, over 80 years of age. Using a battery of functional tests their fitness status was assessed and the subjects were stratified into 5 functional categories according to Spirduso´s classification. Biochemistry analysis was performed by enzymatic method using automated analyzers. APOE gene polymorphism was analysed performed using PCR-RFLP. RESULTS: APOE4 allele carriers had significantly worse fitness status compared to non-carriers (p=0.025). Multiple logistic regression analysis showed the APOE4 carriers had higher risk (p=0.05) of functional unfitness compared to APOE2/E3 individuals. CONCLUSIONS: APOE gene polymorphism seems be an important genetic contributor to frailty development in the elderly. While APOE2 carriers tend to remain functionally fit till higher age, the functional status of APOE4 carriers deteriorates more rapidly.
Keywords: Heterozygote; Apolipoproteins E; senioři nad 80 let; Humans; Logistic Models; lidé; Polymorphism, Genetic; Real-Time Polymerase Chain Reaction; apolipoprotein E4; Aged, 80 and over; apolipoproteiny E; Risk Assessment; dlouhověkost; Longevity; tělesná výkonnost; Female; genetická zdatnost; Apolipoprotein E2; hodnocení rizik; Apolipoprotein E3; Male; Apolipoprotein E4; heterozygot; Physical Fitness; polymorfismus genetický; senioři; Genetic Fitness; apolipoprotein E3; kvantitativní polymerázová řetězová reakce; Aged; Life Expectancy; Nutritional Status; ženské pohlaví; mužské pohlaví; apolipoprotein E2; nutriční stav; naděje dožití; logistické modely